Frequency distributions of hypertext path patterns: A pragmatic approach - Qiu, Liwen (Information processing & management, 1994)
The objective of this research is to discover the path patterns through which users retrieve information in hypertext systems. A pragmatic approach was taken in which the use of a hypertext information retrieval system by a group of subjects was monitored to collect path pattern data. Two frequency distribution models were then developed and tested using these data. Path length followed a shifted negative binomial distribution. The frequency of node visiting followed a Zipf distribution. The influence of search tasks on path patterns was examined and found to have no effect. The models developed and tested in this study can provide a background for examination of systems via simulation studies.